Dual effects of baicalin on osteoclast differentiation and bone resorption. Issue 10 (16th July 2018) - Lu, Xuanyuan; He, Wei; Yang, Wanlei; Li, Jianlei; Han, Weiqi; Liu, Qian; Zhang, Tan; Jiang, Jiawei; Qin, An; Qian, Yu
Abstract: Osteoclasts (OC) are critical cells responsible for many bone diseases such as osteoporosis. It is of great interest to identify agents that can regulate the activity of OC to treat osteolytic bone diseases. In this study, we found that baicalin exerted a two‐way regulatory effect on OC in a concentration‐dependent manner in vitro and in vivo. In detail, baicalin at a low concentration (below 1 μmol/L) enhanced OC differentiation and bone resorption, but baicalin at a high concentration (above 2 μmol/L) exhibited inhibitory effects on OC. We demonstrated that baicalin at low concentrations enhanced the mitogen‐activated protein kinase (MAPK) (ERK) signalling pathway and activated c‐Fos and NFATc1 expression, and thus enhanced gene expression, OC differentiation and bone resorption. However, baicalin at higher levels not only suppressed ERK phosphorylation and c‐fos and NFATc1 expression, but also altered the expression of apoptosis‐related proteins, and therefore inhibiting OC function. This dual effect was further verified in an LPS‐induced mouse calvarial osteolysis model, evidenced by enhanced osteolysis at a lower concentration but reduced bone loss at a higher concentration. Overall, our findings indicate that baicalin exerts dose‐dependent effects on OC formation and function. Therefore, caution should be applied when using baicalin to treating OC‐related bone diseases.